The Students’ Perceptions on Learning Media to Teach in Descriptive Text - Purwanto, Syilviana Eka; Megawati, Fika (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
The goal of this research is to replace the lecture method in junior high school with learning media in the form of animation films for descriptive text learning. The researchers doing the study used both qualitative and quantitative methods. The information for this study was gathered through surveys, interviews, figuring out how people rated things on a Likert scale, and analyzing the themes that came up. The people who were studied were seventh graders. 50 students filled out the form, and 10 students were chosen at random to be interviewed. Using a Likert scale with a percentage of more than 90% in each group, the results of this study were calculated. Coding analysis showed that using cartoon films as a learning tool for students is interesting, memorable, easy to understand, effective, and efficient. Researchers found a common theme, which was interest in science, interest in learning, and wonder. There is also a connection between these ideas. The results of this study should make it easier for students to write what they want to say and help them find new ways to make learning more fun.